PENERAPAN TIME-DRIVEN ACTIVITY BASED COSTING PADA PERHITUNGAN HARGA POKOK KAMAR PENGINAPAN PONDOK IMPIAN - Ryan, Juanelo; Faliany, Lim Jade (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2018)
This research aims to calculate the cost of production of Pondok Impian inn. The method that used in this research is a case study, and the authors do the calculation with Time Driven Activity Based Costing (TDABC). The TDABC calculate cost of production of Pondok Impian, an inn located in RE Martadinata road no.2, West Ancol, North Jakarta. The reseach showed that the TDABC was a suitable method for the inn because it helped calculate the base price of each of its services.